Christian humanism: essays in honour of Arjo Vanderjagt - MacDonald, Alasdair A.; Vanderjagt, Arie Johan (Studies in medieval and Reformation traditions, 2009)
Christianity and humanism. Coluccio Salutati in the footsteps of the ancients / Ron Witt -- Christlicher Humanismus und Liturgie : Heinrich Bebel, Johannes Casselius und Leonhard Clemens verfassen Offizien zu den Festen des heiligen Hieronymus und der heiligen Anna / Volker Honemann -- Rühmende Memoria : der Zusammenhang von Verdiesseitigung und Religiosität in der Gedächtnispflege der Humanisten / Berndt Hamm -- Religion as exercitatio mentis : a case for theology as a humanist discipline / Willemien Otten -- A classicising friar at work : John of Wales' Breviloquium de virtutibus / Albrecht Diem -- Humanism and stoicism. Virtue as an end in itself : the medieval unease with a stoic idea / István P. Bejczy -- Florentius Volusenus and tranquility of mind : some applications of an ancient ideal / Alasdair A. Macdonald -- The first Christian defender of stoic virtue? : Justus Lipsius and Cicero's Paradoxa stoicorum / Jan Papy -- Coornhert on virtue and nobility / Hans and Simone Mooij-Valk -- Humanism and philosophy. The De veritate fidei christianae of Juan Luis Vives / Marcia L. Colish -- Montaigne and Christian humanism / Peter Mack -- Humanism and religion in the works of Spinoza / Fokke Akkerman -- Erasmus of Rotterdam and late medieval theologians on the doctrine of grace / Christoph Burger -- The philosophia Christi, its echoes and its repercussions on virtue and nobility / Han van Ruler -- Modern humanism as philosophical autobiography : pretending and understanding selfhood in Descartes and Fichte / Detlev Pätzold --